Rebellion under the banner of Islam the Darul Islam in Indonesia - Dijk, C. van 1946- (Martinus Nijhoff, 1981)
The Darul Islam rebellion , striving for the establishment of an Islamic State of Indonesia, broke out in several areas since 1949. The author describes each of these Darul Islam rebellions and identifies some of the factors which may help to explain their outbreak and persistence. Ch. 1 sketches life and background of the most important Darul Islam leader: S.M. Kartosuwirjo. In the next five chapters the political history of the relevant regions (West Java, Central Java, South Sulawesi, South Kalimantan and Aceh) and their respective Darul Islam risings are outlined. Ch. 7 discusses the question of why people joined the Darul Islam
Keywords: Geschichte 1949-1962; Darul Islam Movement; Islam and politics; Unruhen; Rebellion; Islam; Darul Islam; Indonesien; 1900 - 1999; Indonesia / History / 20th century; Indonesia; Indonesia / Java; History; Hochschulschrift